Code-Switching Used By Valerie Thomas In The Puella Id Podcast On Youtube - Pratiwi, Shelly Aulia; Ahsani, Nizam (CV. Creative Tugu Pena, 2024)
Code-switching is a phenomenon of switching two or more languages that commonly happens to bilinguals and multilinguals. In this digital era, code-switching can be found in almost all social media platforms, one of them is YouTube. This research aims to identify the types code-switching and analyze the reasons for its occurrence spoken by Valerie Thomas in the Puella Id podcast on YouTube. The research applied Poplack's (1980) and Hoffman's (1991) theories. The research applied a descriptive qualitative method. The data of this research were Valerie Thomas’s utterances in the form of sentences containing code-switching. The data were collected using the observation method (metode Simak) and analyzed using identity method (metode padan) by Sudaryanto (1993). The result showed 45 utterances with code-switching: three types of code-switching: 4 data in tag switching, 35 data in intra-sentential switching, and 6 data in inter-sentential switching. Whereas, six out of 7 reasons for code-switching appeared in this research: 26 data were talking about a particular topic, 2 data were about quoting somebody else, 5 data were being emphatic about something, 4 data were interjections (inserting sentence fillers or sentence connectors), 3 data were repetition used for clarification, and 5 data were the intention of clarifying the speech content for the interlocutor. The researcher did not find any data on expressing group identity.